2020
DOI: 10.1007/s12274-020-2819-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Co and Ce dual-doped Ni3S2 nanosheets on Ni foam for enhanced oxygen evolution reaction

Abstract: Developing efficient and stable oxygen evolution reaction (OER) electrocatalysts via doping strategy has well-documented for electrochemical water splitting. Herein, a homogeneous structure (denoted as Co/Ce-Ni 3 S 2 /NF) composed of Co and Ce dual doped Ni 3 S 2 nanosheets on nickel foam was synthesized by a facile one-step hydrothermal method. Co and Ce dopants are distributed inside the host sulfide, thereby raising the active sites and the electrical conductivity. Besides, the CeO x nanoparticles generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…As shown in Figure S3a, Ni 2p level is split into Ni 2p 3/2 (856.0 eV) and Ni 2p 1/2 (873.8 eV) peaks, coupled with two satellite peaks, which demonstrates the Ni 2+ ions. Moreover, a weaker satellite peak of 852.7 eV could be attributed to the exposed NF matrix. , In Figure S3b, two identical peaks of W 4f 7/2 (35.1 eV) and W 4f 5/2 (37.2 eV) indicate the presence of W 6+ in W-Ni 3 S 2 –0.1/NF . In Figure S3c, the binding energy locations at 161.7, 163.1, 164.1, and 168.4 eV are related to the S 2p 3/2 , S 2p 1/2 , and C–S–C from TAA reactant and highly oxidized sulfur .…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure S3a, Ni 2p level is split into Ni 2p 3/2 (856.0 eV) and Ni 2p 1/2 (873.8 eV) peaks, coupled with two satellite peaks, which demonstrates the Ni 2+ ions. Moreover, a weaker satellite peak of 852.7 eV could be attributed to the exposed NF matrix. , In Figure S3b, two identical peaks of W 4f 7/2 (35.1 eV) and W 4f 5/2 (37.2 eV) indicate the presence of W 6+ in W-Ni 3 S 2 –0.1/NF . In Figure S3c, the binding energy locations at 161.7, 163.1, 164.1, and 168.4 eV are related to the S 2p 3/2 , S 2p 1/2 , and C–S–C from TAA reactant and highly oxidized sulfur .…”
Section: Resultsmentioning
confidence: 94%
“…[102] Furthermore, Wu et al found that the Co and Ce dual-doped Ni 3 S 2 nanosheets outperformed those of single metal doped and undoped Ni 3 S 2 for OER electrocatalysis. [103] Experimental and theoretical results revealed that the Co, Ce dual doping can increase the active sites and conductivity by electronic structure modification.…”
Section: Ceo 2 /Metal Sulfide Composite Catalysts For Oermentioning
confidence: 99%
“…to form heterostructures is also a common way to obtain high OER performance. In addition, Ni 3 S 2 has been doped by several heteroatoms to modulate the band structure for improved catalytic activity, such as N, [ 16 ] Cu, [ 17 ] Co, [ 18,19 ] Mn, [ 20 ] Fe, [ 21 ] Mo, [ 22 ] and others. Although these tactics can boost the OER activity of Ni 3 S 2 to some extent, further improvement relies on subtle design on the adsorption ability of *O and *OOH.…”
Section: Introductionmentioning
confidence: 99%